B.01 AVXS-101 gene-replacement therapy (GRT) for spinal muscular atrophy type 1 (SMA1): pivotal phase 3 study (STR1VE) update. (5th June 2019) - Day, JW; Chiriboga, CA; Crawford, TO; Darras, BT; Finkel, RS; Connolly, AM; Iannaccone, ST; Kuntz, NL; Pena, LD; Schultz, M; Shieh, PB; Smith, EC; et al.
Abstract : Background: SMA1 is a neurodegenerative disease caused by bi-allelic survival motor neuron 1 gene ( SMN1 ) deletion/mutation. In the phase 1 study, SMN GRT onasemnogene abeparvovec (AVXS-101) improved outcomes of symptomatic SMA1 patients. We report preliminary data of STR1VE, a pivotal study (NCT03306277) evaluating efficacy and safety of a one-time intravenous AVXS-101 infusion.Methods: STR1VE is a phase 3, multicenter, open-label, single-arm study in SMA1 patients aged <6 months (bi-allelic SMN1 loss, 2x SMN2 ). Primary outcomes: independent sitting for ≥30 seconds (18 months) and survival (14 months). Secondary outcomes: ability to thrive and ventilatory support (18 months). Exploratory outcomes: CHOP-INTEND and Bayley Scales of Infant and Toddler Development scores.Results: Enrollment is complete with 22 patients dosed. Mean age at symptom onset, genetic diagnosis, and enrollment was 1.9 (0–4.0), 2.1 (0.5–4.0), and 3.7 (0.5–5.9) months. At baseline, no patient required ventilatory/nutritional support, and all exclusively fed by mouth. Mean baseline CHOP-INTEND score was 32.6 (17.0–52.0), which increased 6.9 (-4.0–16.0, n=20), 10.4 (2.0–18.0, n=12), and 11.6 (-3.0–23.0, n=9) points at 1, 2, and 3 months; updates provided at congress.Conclusions: Preliminary data from STR1VE show rapid motor function improvements in SMA1 patients, paralleling phase 1 findings.